(untitled) (KULT_online, 2024)
Gregor Stemmrich’s study of Rauschenberg’s Erased de Kooning Drawing (1953) challenges the prevailing interpretation of the work as an act of iconoclasm, offering a broader perspective. By means of meticulous contextualization and alignment with modern, modernist, and postmodern theories, Stemmrich demonstrates how the work integrates ideas of modernism, literalism, and postmodernism. His analysis expands the interpretation and reassesses its significance in postwar art, thereby making his publication a vital yet challenging contribution to Rauschenberg research and postwar art history.